Trade effects of the East African Customs Union in Tanzania: Application of a structural gravity model - Vincent Leyaro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
By measuring the effects of forming and joining a regional integration bloc using an augmented structural gravity model, this paper finds that the East African Community (EAC) and EAC Customs Union have significantly enhanced Tanzanian trade into EAC markets. Kenya has continued to be the main trading partner for Tanzania in the EAC markets, and from 2015 onwards the trade deficit with Kenya changed into a surplus, signalling improvement in the balance of trade. Tanzania has also maintained a significant trade balance surplus with the other EAC Partner States. There have, however, been no significant changes in Tanzania's trade patterns, which have remained primarily inter-industry rather than intra-industry, signalling a lack of structural change and productivity in the economy and suggesting that Tanzania's trade in EAC markets is not linked with industrialization and transformation. Furthermore, continued trade imbalances, especially with Kenya, threaten a backlash in the long term and are not healthy for the future and sustainability of the EAC integration process.
Keywords: H23; H53; 330; East Africa; EAC Customs Union; single customs territory; gravity model; Tanzania